AN EXPLORATION INTO FACTORS ASSOCIATED WITH READING ANXIETY AMONG TAIWANESE EFL LEARNERS - Tsai, Yea-Ru; Lee, Chun-Yen (TEFLIN Journal, 2018)
The present study was an elaboration on factors influencing for- eign language (FL) reading anxiety in EFL learners (n = 202) in Taiwan. Data were collected from three measures, a background information questionnaire, the Foreign Language Reading Anxiety Scale (FLRAS) and a semi-structured interview. The results showed that FL reading anxiety was associated with time spent on reading English, but not with gender and academic major. Moreover, FL reading anxiety was found to be positively correlated with text features and personal factors, but negatively correlated with reading strategy use, indicating that the more reading strategies a learner employs, the lower FL reading anxiety level he/she will experience. Unfamiliar vocabulary, unknown topics, long and complicated text structure as well as the fear of making mistakes were identified as the major factors of FL reading anxiety. This study contributes to extending our understanding of factors that might evoke EFL reading anxiety.